Peningkatan Ketrampilan Berbicara melalui Layanan Bimbingan Kelompok Teknik Bermain Peran bagi Siswa Kelas XI Teknik Pemesinan-2 SMK Negeri 2 Kebumen Pada Semester 1 Tahun 2015/2016 - Margiyoto, Margiyoto (Jurnal Profesi Keguruan, 2015)
The problems in this study is whether the service of group guidance with role play technique can improve speaking skills class XI student of Mechanical Machining-2 SMK Negeri 2 Kebumen in the 1st half year 2015/2016; What is the procedure implementation guidance services group with role playing techniques performed in class XI-2 Mechanical Machining SMK Negeri 2 Kebumen in the 1st half year 2015/2016; Is there any significant difference before and after using the service of group guidance with role playing techniques in class XI student of Mechanical Machining-2 SMK Negeri 2 Kebumen in the 1st half year 2016. Implementation 201/5 in group counseling techniques of playing this role is done in two cycles, each cycle consists of two rounds, free subject material students do spontaneously and topic assignments made by the counselor. Based on the discussion and in-depth study be concluded that through guidance services group role play technique can improve the skills of speaking of initial conditions 27.80% to 70% so that increased 42.20%.